Half a world apart? Overlap in nonbreeding distributions of Atlantic and Indian Ocean thin-billed prions - Quillfeldt, Petra; Cherel, Yves; Masello, Juan F.; Delord, Karine; McGill, Rona A. R.; Furness, Robert W.; Moodley, Yoshan; Weimerskirch, Henri; Justus Liebig University Giessen (My University, 2015)
Distant populations of animals may share their non-breeding grounds or migrate to distinct areas, and this may have important consequences for population differentiation and dynamics. Small burrow-nesting seabirds provide a suitable case study, as they are often restricted to safe breeding sites on islands, resulting in a patchy breeding distribution. For example, Thin-billed prions Pachyptila belcheri have two major breeding colonies more than 8,000 km apart, on the Falkland Islands in the south-western Atlantic and in the Kerguelen Archipelago in the Indian Ocean. We used geolocators and stable isotopes to compare at-sea movements and trophic levels of these two populations during their non-breeding season, and applied ecological niche models to compare environmental conditions in the habitat. Over three winters, birds breeding in the Atlantic showed a high consistency in their migration routes. Most individuals migrated more than 3000 km eastwards, while very few remained over the Patagonian Shelf. In contrast, all Indian Ocean birds migrated westwards, resulting in an overlapping nonbreeding area in the eastern Atlantic sector of the Southern Ocean. Geolocators and isotopic signature of feathers indicated that prions from the Falklands moulted at slightly higher latitudes than those from Kerguelen Islands. All birds fed on low trophic level prey, most probably crustaceans. The phenology differed notably between the two populations. Falkland birds returned to the Patagonian Shelf after 2-3 months, while Kerguelen birds remained in the nonbreeding area for seven months, before returning to nesting grounds highly synchronously and at high speed. Habitat models identified sea surface temperature and chlorophyll a concentration as important environmental parameters. In summary, we show that even though the two very distant populations migrate to roughly the same area to moult, they have distinct wintering strategies: They had significantly different realized niches and timing which may contribute to spatial niche partitioning.
Keywords: ddc:570